Method for producing tantalum powder by using tantalum metallurgy byproducts
By reacting potassium fluorotantalate and tantalum metallurgy by-products with sodium during the tantalum metallurgy process, and distilling and separation of sodium, the problem of poor treatment of by-products in traditional technology is solved, and efficient utilization of resources and environmentally friendly production process is achieved.
Patent Information
- Application Number
- CN202510137606.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-07
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2045-02-07
AI Technical Summary
In traditional tantalum metallurgy technology, poor treatment of by-products leads to the wastewater containing harmful ions, polluting the environment, and low resource utilization efficiency.
By mixing potassium fluortanate and tantalum metallurgy by-products and reacting with sodium at high temperature, then sodium distillation is performed to remove excess sodium, and finally tantalum powder and secondary by-products are separated, crushed and dried to form a recyclable diluent.
It realizes effective recycling and reuse of by-products, reduces production costs, reduces environmental pollution, and improves the direct yield of tantalum powder, meeting the industry standards of metallurgical tantalum powder.
Smart Images

Figure BDA0005263757950000061
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of tantalum metallurgy, and in particular to a method for producing tantalum powder by utilizing tantalum metallurgy byproducts. Background Art
[0002] The reduction of potassium sodium fluorotantalate to produce tantalum powder is a method of using potassium fluorotantalate and sodium as the main raw materials and using halide salts such as sodium chloride, potassium chloride, potassium fluoride or halide salt mixtures as diluents to prepare tantalum powder. The main reaction mechanism is as follows:
[0003] K2TaF7+5Na=Ta+5NaF+2KF
[0004] Under argon protection and at a certain temperature, K2TaF7 reacts with liquid sodium as described above. This reaction is an exothermic reaction. When the reaction starts, a large amount of heat is released, making the reaction rate too fast. Therefore, the control of the reaction rate depends on the heat absorption of the above-mentioned halide salt or halide salt mixture. The above-mentioned halide salt does not participate in the chemical reaction during the entire reduction process. In the actual production process, controlling the reduction process by controlling the heating curve is the key link to ultimately control the performance of tantalum powder. The obtained tantalum powder is washed with water and acid washed, then heat treated, and then reduced and deoxidized by magnesium to obtain the final tantalum powder.
[0005] Therefore, the by-product of tantalum metallurgy is a mixture of sodium fluoride, potassium fluoride and the originally added diluent halide salt, which generally appears as a purple porous block with light blue and white, and is highly corrosive. The sodium reduction method for making tantalum powder uses one or more of sodium chloride, potassium chloride and potassium fluoride as diluents, and uses metallic sodium to reduce potassium tantalate to obtain tantalum powder. The by-product is a molten salt mixture, the main components of which are sodium chloride, potassium chloride, potassium fluoride and sodium fluoride, containing recyclable ultrafine tantalum powder and trace oxides.
[0006] The traditional treatment method in China is to concentrate the by-products in a large wastewater pool, dissolve them with the wastewater generated by the subsequent tantalum powder purification process, extract the ultrafine tantalum powder and oxides in the filter residue, and send them to wet extraction to recover tantalum. However, the wastewater contains a large amount of F - , Cl - Ions are harmful to the environment and cannot be discharged at will. Summary of the invention
[0007] In order to solve the above technical problems, the present invention provides a method for producing tantalum powder using tantalum metallurgical byproducts. The specific technical solution is as follows:
[0008] A method for producing tantalum powder using tantalum metallurgical byproducts, wherein the tantalum metallurgy uses at least one of sodium chloride, potassium chloride and potassium fluoride as a diluent, and tantalum is produced by reducing potassium fluorotantalate with sodium, and the method comprises the following steps:
[0009] Step 1: Mix potassium fluorotantalate and tantalum metallurgical by-products evenly and load them into a reactor, and then add sodium;
[0010] Step 2: heating the reaction furnace to 600-750° C. to react potassium tantalate and sodium;
[0011] Step 3: After the reaction is completed, the temperature in the furnace is adjusted to 850-950° C. for sodium distillation, and the sodium vapor is introduced into a condenser;
[0012] Step 4: After the sodium distillation is completed, the temperature in the reaction furnace is adjusted to room temperature and the reactants are taken out;
[0013] Step 5: Separate the tantalum powder and secondary by-products in the reactants, and crush and dry the separated secondary by-products for use as the tantalum metallurgical by-products in step 1.
[0014] Preferably, the separation method of tantalum powder and secondary by-products in step 5 is mechanical separation or manual separation; the separated secondary by-products are crushed into solid blocks with a particle size of 40 to 55 mm by a jaw crusher.
[0015] Preferably, the secondary by-product separated in step 5 is dried in a F- and Cl-corrosion resistant vacuum oven at a drying temperature of 100 to 200° C. for a drying time of 5 to 30 hours.
[0016] Preferably, the water content of the secondary by-product after drying in step 5 is ≤0.05%.
[0017] Preferably, in step 1, the mixing ratio of potassium fluorotantalate and tantalum metallurgical by-product is 1:(2-10).
[0018] Preferably, the reaction in step 2 is carried out under an argon protective atmosphere or under an argon flowing atmosphere.
[0019] Preferably, the condensation tank in step 3 is a three-stage condensation tower structure, which includes an upper condensation zone, a middle condensation zone and a lower condensation zone from top to bottom, the temperature of the upper condensation zone is 400-500°C, the temperature of the middle condensation zone is 300-400°C, and the temperature of the lower condensation zone is 100-150°C.
[0020] Preferably, the tantalum metallurgical byproducts in step 1 may also be mixed with a ceramic-conductive molecule composite catalyst, wherein the ceramic-conductive molecule composite catalyst is formed by composite of a ceramic material and a conductive polymer or a ceramic material and a metal oxide.
[0021] Preferably, the ceramic-conductive molecule composite catalyst is formed by composite ceramic material and conductive polymer, and its preparation process comprises the following steps:
[0022] The aluminum oxide powder is calcined at 700-800° C., and then added into deionized water, and dispersed evenly to obtain an aluminum oxide suspension.
[0023] The pyrrole monomer and ammonium persulfate are dissolved in a solvent to prepare polypyrrole;
[0024] The aluminum oxide suspension is added to the synthesis reaction solution of polypyrrole, and the excess solvent is removed by filtering after stirring or ultrasonic treatment to obtain a composite material of polypyrrole loaded with aluminum oxide;
[0025] The obtained composite material was dried at 60-80°C for 12h to remove the solvent;
[0026] The composite material is obtained by heat treating the composite material at 300-500°C.
[0027] Preferably, the ceramic-conductive molecule composite catalyst is formed by combining a ceramic material with a metal oxide, and its preparation process includes the following steps:
[0028] The aluminum oxide powder is calcined at 700-800°C;
[0029] Dissolve cerium nitrate in deionized water, and add ammonia water to adjust the pH to 8-9;
[0030] After drying, calcining at 600-700°C for 4 hours to obtain cerium oxide;
[0031] The cerium oxide and the calcined alumina powder are mixed uniformly in a mass ratio of 1:1, and then added into deionized water to form a composite slurry, and then dispersed uniformly by stirring or ultrasonication;
[0032] The composite slurry is dried at 60-100° C. for 12 hours, and then sintered at 800-1000° C. for 3-5 hours to obtain the composite slurry.
[0033] The method for producing tantalum powder using tantalum metallurgical byproducts provided by the present invention has the following beneficial effects:
[0034] 1. Utilize the by-products produced in the tantalum metallurgical production process to remove residual sodium through distillation, clarify and separate, crush and dry, and then directly use them as diluents for the reduction of potassium sodium fluorotantalate, which can reduce the melting point of molten salt and achieve energy saving.
[0035] 2. Since the composite salt contains ultrafine tantalum powder and tantalum oxide, the direct recovery rate of tantalum powder can be effectively improved.
[0036] 3. It realizes the recycling of waste resources and reduces environmental pollution. The tantalum powder produced meets the industry standards of metallurgical tantalum powder, which is both environmentally friendly and saves production costs. DETAILED DESCRIPTION
[0037] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is described in detail below. The description in this section is only exemplary and explanatory and should not have any limiting effect on the scope of protection of the present invention.
[0038] This embodiment provides a method for producing tantalum powder using tantalum metallurgical byproducts. Tantalum metallurgy uses at least one of sodium chloride, potassium chloride, and potassium fluoride as a diluent, and tantalum is produced by reducing potassium fluorotantalate with sodium. The method includes the following steps:
[0039] Step 1: Mix potassium fluorotantalate and tantalum metallurgical by-products evenly and load them into a reactor, and then add sodium.
[0040] Step 2: Heat the reaction furnace to 600-750°C to react potassium tantalate and sodium.
[0041] Step 3: After the reaction is completed, the temperature in the furnace is adjusted to 850-950°C for sodium distillation, and the sodium vapor is introduced into the condensation tank.
[0042] Step 4: After the sodium distillation is completed, adjust the temperature in the reactor to room temperature and take out the reactants.
[0043] Step 5: Separate the tantalum powder and secondary by-products in the reactants, and crush and dry the separated secondary by-products for use as the tantalum metallurgical by-products in step 1.
[0044] Among them, the by-products obtained by the sodium reduction method of potassium fluorotantalate to produce tantalum powder mainly include sodium fluoride and potassium fluoride. Potassium fluorotantalate and tantalum metallurgical by-products are mixed evenly and put into a reactor, and sodium is added. At a temperature of 600-750°C, sodium will react with potassium fluorotantalate to reduce tantalum in potassium fluorotantalate to tantalum metal. In this process, sodium acts as a reducing agent to separate tantalum from fluoride to produce tantalum powder, sodium fluoride and potassium fluoride.
[0045] When the reduction reaction is completed, the furnace temperature is adjusted to 850-950℃ and sodium distillation begins. Sodium distillation can evaporate excess sodium to prevent it from interfering with subsequent operations. Sodium vapor will evaporate from the furnace at high temperature and enter the condensation tank for condensation recovery. Sodium distillation can effectively remove excess sodium in the reaction and obtain purer tantalum powder.
[0046] After the distillation is completed, the furnace temperature is adjusted to 300-400°C and the reactants are taken out. At this time, the tantalum in the potassium fluorotantalate has been reduced to a solidified block of metallic tantalum powder, and the sodium has been evaporated. Low temperature helps to control the tantalum extraction process and prevent further reaction between tantalum powder and other substances. In step 5, the tantalum powder in the reactants is separated from the secondary by-products. Tantalum powder is usually separated by physical methods (such as screening, sedimentation, etc.). After crushing and drying, the secondary by-products can be reused as tantalum metallurgical by-products in the raw materials of step 1 for recycling.
[0047] In the process of sodium reducing potassium fluorotantalate, sodium, as a reducing agent, can effectively reduce tantalum metal from potassium fluorotantalate, and remove excess sodium through high-temperature distillation to obtain high-purity tantalum powder. Through step 5, the secondary by-products can be recycled to achieve efficient utilization of resources.
[0048] The method for producing tantalum powder using tantalum metallurgical byproducts provided in this embodiment has the following beneficial effects:
[0049] 1. Utilize the by-products produced in the tantalum metallurgical production process to remove residual sodium through distillation, clarify and separate, crush and dry, and then directly use them as diluents for the reduction of potassium sodium fluorotantalate, which can reduce the melting point of molten salt and achieve energy saving.
[0050] 2. Since the composite salt contains ultrafine tantalum powder and tantalum oxide, the direct recovery rate of tantalum powder can be effectively improved.
[0051] 3. It realizes the recycling of waste resources and reduces environmental pollution. The tantalum powder produced meets the industry standards of metallurgical tantalum powder, which is both environmentally friendly and saves production costs.
[0052] Furthermore, the separation method of the tantalum powder and the secondary by-products in step 5 is mechanical separation or manual separation. The separated secondary by-products are crushed into solid blocks with a particle size of 40 to 55 mm by a jaw crusher.
[0053] Among them, tantalum powder has a higher density and is usually heavier than other by-products. Therefore, tantalum powder and secondary by-products can be separated by physical separation using methods such as vibrating screens and airflow sorting. Artificial separation can be carried out by manual screening, manual picking, etc. to separate pure tantalum powder.
[0054] The separated secondary by-products are crushed by a jaw crusher to obtain solid blocks with a particle size of 40 to 55 mm. These solid blocks will enter step 1 as raw materials for the next round of reaction, realizing the recycling of tantalum metallurgical by-products.
[0055] The by-products after crushing usually need to be dried to remove moisture or volatile substances in them, making the by-products more suitable for entering the smelting process again.
[0056] Further, the secondary by-product separated in step 5 is subjected to F-resistant - , Cl - The corrosion vacuum oven is used for drying, the drying temperature is 100-200°C, and the drying time is 5-30h.
[0057] Among them, the F- and Cl-resistant vacuum oven is a specially designed equipment that can resist the corrosion of fluoride ions (F-) and chloride ions (Cl-). This is because the fluorides and chlorides in the by-products of tantalum metallurgy are highly corrosive and conventional ovens may not be able to withstand them.
[0058] The drying temperature is set within the temperature range of 100 to 200° C., which can effectively remove moisture or volatile substances in the secondary by-products without causing the tantalum or other components in the by-products to decompose or deteriorate.
[0059] The drying time is set between 5 and 30 hours, and the specific time is adjusted according to the moisture content and properties of the by-products. 5 hours is suitable for by-products with lower moisture content or looser by-products, and 30 hours is suitable for by-products with higher moisture content or higher density, and the drying process is slower.
[0060] Furthermore, the water content of the secondary by-product after drying in step 5 is ≤0.05%.
[0061] Furthermore, in step 1, the mixing ratio of potassium fluorotantalate and tantalum metallurgical byproducts is 1:(2-10), which can improve the utilization rate of reactants in the reaction process and ensure that tantalum can be effectively extracted from the byproducts. The amount of potassium fluorotantalate is small, while the amount of tantalum metallurgical byproducts is large. More byproducts can ensure that sufficient tantalum sources participate in the reaction and provide sufficient raw materials for subsequent tantalum extraction.
[0062] The mixing ratio of the reactants will directly affect the subsequent tantalum reduction efficiency and the purity of the tantalum powder. This ratio can optimize the reaction conditions, improve the tantalum extraction efficiency, and maximize the resource utilization during the reaction. During the process implementation, the specific ratio needs to be reasonably adjusted according to the nature of the by-products and the amount of potassium fluorotantalate.
[0063] Furthermore, the reaction in step 2 is carried out under an argon protective atmosphere or under an argon flowing atmosphere.
[0064] Among them, the argon protective atmosphere can effectively reduce the oxidation of metals such as sodium and tantalum, and improve the selectivity and efficiency of the reduction reaction; the argon flow can promote the timely discharge of the reaction gas, avoiding gas accumulation leading to incomplete reaction or accumulation of by-products.
[0065] Furthermore, the condensation tank in step 3 is a three-stage condensation tower structure, which includes an upper condensation zone, a middle condensation zone and a lower condensation zone from top to bottom. The temperature of the upper condensation zone is 400-500°C, the temperature of the middle condensation zone is 300-400°C, and the temperature of the lower condensation zone is 100-150°C.
[0066] Among them, the three-stage condensation tower is usually a multi-stage segmented condensation system, which condenses sodium vapor into liquid sodium in different temperature ranges by gradually lowering the temperature and avoids mixing of sodium vapor with other substances.
[0067] Furthermore, the tantalum metallurgical byproducts in step 1 may also be mixed with a ceramic-conductive molecule composite catalyst, and the ceramic-conductive molecule composite catalyst is formed by composite of a ceramic material and a conductive polymer or a ceramic material and a metal oxide.
[0068] Among them, the catalyst is formed by compounding a conductive polymer or metal oxide with a ceramic material. The ceramic material is used as a catalyst carrier, combining its good thermal stability, chemical stability and high specific surface area with a conductive or catalytically active polymer, metal oxide or metal nanoparticle, which can effectively improve the conductivity, catalytic activity and thermal stability of the catalyst. These composite materials can provide good catalytic performance and effectively accelerate the reduction reaction in the high temperature environment of sodium reduction of potassium fluorotantalate.
[0069] Furthermore, the ceramic-conductive molecule composite catalyst is formed by combining a ceramic material with a conductive polymer, and its preparation process includes the following steps:
[0070] Alumina powder is calcined at 700-800° C., added into deionized water, and dispersed evenly to obtain an alumina suspension.
[0071] The pyrrole monomer and ammonium persulfate are dissolved in a solvent to prepare polypyrrole.
[0072] The aluminum oxide suspension is added into the synthetic reaction solution of polypyrrole, and the excess solvent is removed by filtering after stirring or ultrasonic treatment to obtain a composite material of polypyrrole loaded with aluminum oxide.
[0073] The obtained composite material was dried at 60-80° C. for 12 h and then the solvent was removed.
[0074] The composite material is obtained by heat treating the composite material at 300-500°C.
[0075] Furthermore, the ceramic-conductive molecule composite catalyst is formed by combining a ceramic material with a metal oxide, and its preparation process includes the following steps:
[0076] The alumina powder is calcined at 700-800°C.
[0077] Dissolve cerium nitrate in deionized water, and add ammonia water to adjust the pH to 8-9.
[0078] After drying, the mixture is calcined at 600-700°C for 4 hours to obtain cerium oxide.
[0079] The cerium oxide and the calcined aluminum oxide powder are mixed evenly in a mass ratio of 1:1, and then added into deionized water to form a composite slurry, and then dispersed evenly by stirring or ultrasonication.
[0080] The composite slurry is dried at 60-100°C for 12 hours, and then sintered at 800-1000°C for 3-5 hours to obtain the composite slurry.
[0081] Specific examples are provided below. The provided examples may enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way.
[0082] Example 1
[0083] Tantalum powder is produced by liquid-liquid stirring sodium reduction process using sodium chloride as diluent and potassium fluorotantalate as raw material. After sodium injection, the reaction is continued for 4 hours. The residual sodium is removed by sodium distillation process. Stirring is stopped and constant temperature is maintained for a certain period of time to ensure that the tantalum powder and by-products are separated. After cooling, the tantalum powder and by-products are separated and crushed into small pieces with a particle diameter of about 50 mm using a jaw crusher. The drying equipment is used to prepare the tantalum powder. - , Cl - The corrosion vacuum oven was dried at 150°C for 15 hours, and the moisture content was analyzed. 60 kg of the dried composite salt was weighed as a diluent, and the tantalum powder was produced according to the process requirements of sodium reduction of potassium fluorotantalate. The results of the obtained tantalum powder are shown in Table 1.
[0084] Example 2
[0085] Tantalum powder is produced by liquid-liquid stirring sodium reduction process using potassium chloride as diluent and potassium fluorotantalate as raw material. After the sodium injection is completed, the reaction is carried out for 4 hours. The residual sodium is removed by sodium distillation process. The stirring is stopped and the temperature is kept constant for a certain period of time to ensure that the tantalum powder and the by-products are separated. After cooling, the tantalum powder and the by-products are separated and crushed into small pieces with a particle diameter of about 50 mm by a jaw crusher. The drying equipment is used to prepare the tantalum powder. - , Cl - The corrosion vacuum oven was dried at 150°C for 15 hours, and the moisture content was analyzed. 60 kg of the dried composite salt was weighed as a diluent, and the tantalum powder was produced according to the process requirements of sodium reduction of potassium fluorotantalate. The results of the obtained tantalum powder are shown in Table 1.
[0086] Example 3
[0087] Tantalum powder is produced by liquid-liquid stirring sodium reduction process using sodium chloride and potassium chloride as diluents and potassium fluorotantalate as raw materials. After sodium injection, the reaction is continued for 4 hours. The residual sodium is removed by sodium distillation. The stirring is stopped and the temperature is kept constant for a certain period of time to ensure that the tantalum powder and the by-products are separated. After cooling, the tantalum powder and the by-products are separated and crushed into small pieces with a particle diameter of about 50 mm using a jaw crusher. The drying equipment is used to prepare the tantalum powder. - , Cl -The corrosion vacuum oven was dried at 150°C for 15 hours, and the moisture content was analyzed. 60 kg of the dried composite salt was weighed as a diluent, and the tantalum powder was produced according to the process requirements of sodium reduction of potassium fluorotantalate. The results of the obtained tantalum powder are shown in Table 1.
[0088] Example 4
[0089] Tantalum powder is produced by liquid-liquid stirring sodium reduction process using potassium chloride and potassium fluoride as diluents and potassium fluorotantalate as raw materials. After the sodium injection is completed, the reaction is carried out for 4 hours, and the residual sodium is removed by sodium distillation process. The stirring is stopped and the temperature is kept constant for a certain period of time to ensure that the tantalum powder and the by-products are separated. After cooling, the tantalum powder and the by-products are separated and crushed into small pieces with a particle diameter of about 50mm by a jaw crusher. The drying equipment is used to prepare the tantalum powder. - , Cl - The corrosion vacuum oven was dried at 150°C for 15 hours, and the moisture content was analyzed. 60 kg of the dried composite salt was weighed as a diluent, and the tantalum powder was produced according to the process requirements of sodium reduction of potassium fluorotantalate. The results of the obtained tantalum powder are shown in Table 1.
[0090] Comparative Example 1
[0091] Alumina powder is calcined at 800°C and then added into deionized water, and then polypyrrole is added, and the mixture is ultrasonically treated, filtered and dried to obtain a ceramic-conductive molecule composite catalyst.
[0092] Sodium chloride is used as a diluent, potassium fluorotantalate is used as a raw material, and the prepared ceramic-conductive molecule composite catalyst is added to produce tantalum powder through a liquid-liquid stirring sodium reduction process. After the sodium injection is completed, the reaction is carried out for 3 hours, and the reaction time is shortened by 25%. The residual sodium is removed through a sodium distillation process, and the stirring is stopped for a certain period of time to ensure that the tantalum powder and the by-products are separated. After cooling, the tantalum powder and the by-products are separated and crushed into small pieces with a particle diameter of about 50 mm using a jaw crusher. The drying equipment is a vacuum oven resistant to F- and Cl- corrosion, the drying temperature is 150°C, the time is 15 hours, and the moisture is analyzed. Weigh 60 kg of the dried composite salt as a diluent, and produce it according to the process requirements for producing tantalum powder by reducing potassium fluorotantalate with sodium. The results of the obtained tantalum powder are shown in Table 1.
[0093] Comparative Example 2
[0094] Alumina powder was calcined at 800°C, mixed evenly with cerium oxide in a mass ratio of 1:1, added into deionized water, dispersed evenly by ultrasonication, dried for 12 hours, and sintered at 1000°C for 5 hours to obtain a ceramic-conductive molecule composite catalyst.
[0095] Sodium chloride is used as a diluent, potassium fluorotantalate is used as a raw material, and then the prepared ceramic-conductive molecule composite catalyst is added to produce tantalum powder through a liquid-liquid stirring sodium reduction process. After the sodium injection is completed, the reaction is carried out for 2.5 hours, and the reaction time is shortened by 37.5%. The residual sodium is removed through a sodium distillation process, and the stirring is stopped and the constant temperature is maintained for a certain period of time to ensure that the tantalum powder and the by-products are separated. After cooling, the tantalum powder and the by-products are separated and crushed into small pieces with a particle diameter of about 50 mm using a jaw crusher. The drying equipment used is a vacuum oven resistant to F- and Cl- corrosion, the drying temperature is 150°C, the time is 15 hours, and the moisture is analyzed. Weigh 60 kg of the dried composite salt as a diluent, and produce it according to the process requirements for producing tantalum powder by reducing potassium fluorotantalate with sodium. The results of the obtained tantalum powder are shown in Table 1
[0096] Table 1: Tantalum powder analysis results Unit: %
[0097]
[0098]
[0099] The principles and implementation methods of the present invention are described herein using specific examples, and the description of the above embodiments is only used to help understand the method and core ideas of the present invention. The above are only preferred implementations of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, can make equivalent replacements or changes according to the technical solutions and inventive concepts of the present invention, which should be within the protection scope of the present invention.
Claims
1. A method for producing tantalum powder using tantalum metallurgical byproducts, characterized in that: The tantalum metallurgy uses at least one of sodium chloride, potassium chloride and potassium fluoride as a diluent, and produces tantalum by reducing potassium fluorotantalate with sodium. The method comprises the following steps: S1: Mix potassium fluorotantalate and tantalum metallurgical by-products evenly and load them into a reactor, and then add sodium; S2: heating the reaction furnace to 600-750°C to react potassium tantalate and sodium; S3: After the reaction is completed, the temperature in the furnace is adjusted to 850-950° C. to perform sodium distillation, and the sodium vapor is introduced into a condensation tank; S4: After the sodium distillation is completed, the temperature in the reaction furnace is adjusted to room temperature and the reactants are taken out; S5: separating tantalum powder and secondary by-products from the reactants, and crushing and drying the separated secondary by-products to be used as the tantalum metallurgical by-products in step S1.
2. The method according to claim 1, characterized in that In step S5, the tantalum powder and the secondary by-products are separated by mechanical separation or manual separation; the separated secondary by-products are crushed into solid blocks with a particle size of 40 to 55 mm by a jaw crusher.
3. The method according to claim 1, characterized in that The secondary byproduct separated in step S5 is subjected to F-resistant - , Cl - The corrosion vacuum oven is used for drying, the drying temperature is 100-200°C, and the drying time is 5-30h.
4. The method according to claim 1, characterized in that: The water content of the secondary by-product after drying in step S5 is ≤0.05%.
5. The method according to claim 1, characterized in that In step S1, the mixing ratio of potassium fluorotantalate and tantalum metallurgical by-product is 1:(2-10).
6. The method according to claim 1, characterized in that The reaction in step S2 is carried out under an argon protective atmosphere or under an argon flowing atmosphere.
7. The method according to claim 1, characterized in that The condensation tank in step S3 is a three-stage condensation tower structure, which includes an upper condensation zone, a middle condensation zone and a lower condensation zone from top to bottom. The temperature of the upper condensation zone is 400-500°C, the temperature of the middle condensation zone is 300-400°C, and the temperature of the lower condensation zone is 100-150°C.
8. The method according to claim 1, characterized in that The tantalum metallurgical byproducts in step S1 may also be mixed with a ceramic-conductive molecule composite catalyst, wherein the ceramic-conductive molecule composite catalyst is formed by composite of a ceramic material and a conductive polymer or a ceramic material and a metal oxide.
9. The method according to claim 8, characterized in that The ceramic-conductive molecule composite catalyst is formed by combining a ceramic material with a conductive polymer, and its preparation process includes the following steps: The aluminum oxide powder is calcined at 700-800° C., and then added into deionized water, and dispersed evenly to obtain an aluminum oxide suspension. The pyrrole monomer and ammonium persulfate are dissolved in a solvent to prepare polypyrrole; The aluminum oxide suspension is added to the synthesis reaction solution of polypyrrole, and the excess solvent is removed by filtering after stirring or ultrasonic treatment to obtain a composite material of polypyrrole loaded with aluminum oxide; The obtained composite material was dried at 60-80°C for 12h to remove the solvent; The composite material is obtained by heat treating the composite material at 300-500°C.
10. The method according to claim 8, characterized in that The ceramic-conductive molecule composite catalyst is formed by combining a ceramic material with a metal oxide, and its preparation process includes the following steps: The aluminum oxide powder is calcined at 700-800°C; Dissolve cerium nitrate in deionized water, and add ammonia water to adjust the pH to 8-9; After drying, calcining at 600-700°C for 4 hours to obtain cerium oxide; The cerium oxide and the calcined alumina powder are mixed uniformly in a mass ratio of 1:1, and then added into deionized water to form a composite slurry, and then dispersed uniformly by stirring or ultrasonication; The composite slurry is dried at 60-100° C. for 12 hours, and then sintered at 800-1000° C. for 3-5 hours to obtain the composite slurry.
Citation Information
Patent Citations
Three-dimensional (3D) printing
CN109414763A
Ta metallurgical by-product composite salt recycling method
CN109468473A
Reguline metal sodium prilling granulator
CN207533972U
Production of tantalum powder
US2950185A
Tantalum production via a reduction of K2TAF7, with diluent salt, with reducing agent provided in a fast series of slug additions
US5442978A